A Sociotechnical Approach to Successful Electronic Health Record Implementation: Five Best Practices for Clinical Nurse Specialists - Irizarry, Taya (Clin Nurse Spec, 2013)
Rising healthcare costs coupled with patient safety considerations and quality of care have become major concerns for healthcare purchasers, providers, and policymakers. Health information technology, particularly the electronic health record (EHR), is posed as a solution to address these concerns by delivering greater efficiencies and improved quality of care. Despite the national movement toward EHR adoption, successful EHR implementation continues to be challenging for many healthcare organizations, both large and small. This article uses sociotechnical systems theory as a framework to discuss 5 best practice guidelines for EHR implementation and outlines what clinical nurse specialists can do to make the process successful.